The Dating of Žemaitė's Autographs - Umbrasas, Kazys (Literatūra, 1970)
This publication gives a complete list of the autographs belonging to the Lithuanian authoress Žemaitė (1845-1921) and defines their precise dates, thus correcting previous mistakes in the dating of her literary works and essays. The development of Žemaitė's orthography has been chosen as the basic principle of dating. The final chapter of this publication corrects mistakes that have occurred in recent editions of letters by Žemaitė and Višinskis (1875-1906).
Keywords: -